Risk factors for chronic lung disease and asthma differ among children born extremely preterm. Issue 11 (29th August 2018) - Jackson, Wesley M.; O'Shea, Thomas Michael; Allred, Elizabeth N.; Laughon, Matthew M.; Gower, William Adam; Leviton, Alan
Abstract : Objectives: To evaluate the hypothesis that chronic lung disease of prematurity (CLD) is a risk factor for asthma in children born extremely preterm, and the hypothesis that the risk factors for CLD are similar to those for asthma. Methods: A retrospective analysis was performed using data collected prospectively from 882 children born before the 28th week of gestation between 2002 and 2004 who returned for follow‐up at ages 12 and 24 months and 10 years. We created time‐oriented logistic regression models to compare risk factors for CLD, defined as need for supplemental oxygen at 36 weeks postmenstrual age, and parent‐reported asthma at 10 years of age. Results: CLD diagnosed during neonatal admission was associated with bronchodilator use at 12 months and 24 months ( P  < 0.001), but not with an asthma diagnosis at 10 years (Odds Ratio 1.3; 95% confidence interval 0.98‐1.8). While risk factors for CLD include lower gestational age (OR 2.7; 1.5‐4.7) and fetal growth restriction (OR 2.3; 1.4‐3.7), risk factors for asthma include mother's eligibility for public insurance (Medicaid) (OR 1.8; 1.1‐2.8), and higher weight gain velocity during the first year (OR 1.5; 1.02‐2.2) and between the 2nd and 10th year (OR 1.7; 1.2‐2.4). Conclusions: Among children born extremely preterm, the diagnosis of CLD and its antecedents were associated with transient preschool wheezing, but not with asthma. Post‐NICU factors, such as growth velocity and socioeconomic disadvantage, appear to have stronger associations with asthma than exposures during NICU admission.